aPKC Phosphorylation of Bazooka Defines the Apical/Lateral Border in Drosophila Epithelial Cells - Eurico Morais‐de‐Sá; Vincent Mirouse; Daniel St Johnston (2010)
Bazooka (PAR-3), PAR-6, and aPKC form a complex that plays a key role in the polarization of many cell types. In epithelial cells, however, Bazooka localizes below PAR-6 and aPKC at the apical/lateral junction. Here, we show that Baz is excluded from the apical aPKC domain in epithelia by aPKC phosphorylation, which disrupts the Baz/aPKC interaction. Removal of Baz from the complex is epithelial-specific because it also requires the Crumbs complex, which prevents the Baz/PAR-6 interaction. In the absence of Crumbs or aPKC phosphorylation of Baz, mislocalized Baz recruits adherens junction components apically, leading to a loss of the apical domain and an expansion of lateral. Thus, apical exclusion of Baz by Crumbs and aPKC defines the apical/lateral border. Although Baz acts as an aPKC targeting and specificity factor in nonepithelial cells, our results reveal that it performs a complementary function in positioning the adherens junction in epithelia.